Study of Percentage of Moisture and Ash Content of Argemone Mexicana and Solubilities in Different Solvents - Tayade, D.T.; Shaikh, R.S. (Asian Journal of Chemistry, 2010)
The percentage of ash and moisture in roots and flowers along with the solubilities of Argemone mexicana in different solvents are described.